ZAKAT HASIL BUNGA BANK DALAM PERSPEKTIF HUKUM ISLAM - Sri Wahyuni (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2021)
This study aims to: (1) find out the views of Islamic law on bank interest and usury (2). Analyzing the perspective of Islamic law on zakat from bank interest results. This study uses a qualitative approach with the type of library research. Then the analysis uses descriptive analysis and content analysis. With this research, it was found that there were many differences of opinion between the scholars and the thoughts of the figures regarding usury and bank interest. Therefore, zakat from interest results depends on the understanding and stability of the person concerned with the law of bank interest. If he believes that bank interest is unlawful because it is equated with usury, then zakat on bank interest is unlawful. If you believe that bank interest is different from usury and the law is not haram, as long as there is no extortion, then zakat on bank interest is not haram. However, if you are in doubt and think that bank interest is doubtful (vague), then the law of zakat on bank interest is doubtful, and whoever is in the area of ​​doubt is in a dangerous area and the law is unlawful. As a material for reflection and consideration related to bank interest, the author is more inclined to bank interest which is not the same as usury. Riba all scholars forbid both small and large additions. Bank interest can be called usury, and also not usury.